Landslide Zonation at the Budong-Budong Watershed, Central Mamuju District of West Sulawesi Province - Solle, Muchtar S; Paharuddin, Paharuddin; Ahmad, Asmita; Ansar, Muh. (Universitas Muhammadiyah Surakarta, 2014)
The objectives of this study are as follows: first, to investigate the contributing parameters induced land sliding in the Budong-Budong watershed, and second, to construct landslide susceptibility zonation map. In this study, the analytical hierarchy process (AHP) based on Geographical Information System (GIS) methods was used to produce map of landslide susceptibility. In this study area, more than 50% of total area were classified high (H) to very high (VH) susceptibility landslide zone. Mean while, 12% of total area were classified as moderate (M) and remaining were classified as low (L) to very low (VL) susceptibility landslide zone. Almost area of Budong-Budong Wetershed were classified as VH and H susceptibility landslide zone underlying by Talaya (Tmtv), Lamasi (Toml) and Latimojong (Kls) Formation on the steep slope land.